2015
DOI: 10.1185/03007995.2015.1062356
|View full text |Cite
|
Sign up to set email alerts
|

Costs, resource utilization, and treatment patterns for patients with metastatic melanoma in a commercially insured setting

Abstract: The cost and resource utilization burden of MM is high and varies substantially across treatment cohorts. The two novel therapies, ipilimumab and vemurafenib, have quickly been adopted and are the most frequently used therapies. The results observed during the approximately 6 month follow-up period may not be representative of the full clinical experience of patients with MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…In the population examined in the current study, temozolomide is more commonly used (19%) than in Toy et al, although both uses were lower than that reported in an earlier study of melanoma treatment patterns between 2005 and 2010, which found that 49% of patients received temozolomide (22). Patients receiving vemurafenib were slightly younger than those receiving ipilimumab, in agreement with the findings from Toy et al (21). The current study reported longer treatment duration for vemurafenib (mean: 174 days) than that reported in Of the patients receiving ipilimumab, 58% received all four doses; this was slightly lower than that of the population from the ipilimumab pivotal Phase III clinical trial, in which 64% of patients received all four doses of ipilimumab (15).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the population examined in the current study, temozolomide is more commonly used (19%) than in Toy et al, although both uses were lower than that reported in an earlier study of melanoma treatment patterns between 2005 and 2010, which found that 49% of patients received temozolomide (22). Patients receiving vemurafenib were slightly younger than those receiving ipilimumab, in agreement with the findings from Toy et al (21). The current study reported longer treatment duration for vemurafenib (mean: 174 days) than that reported in Of the patients receiving ipilimumab, 58% received all four doses; this was slightly lower than that of the population from the ipilimumab pivotal Phase III clinical trial, in which 64% of patients received all four doses of ipilimumab (15).…”
Section: Discussionsupporting
confidence: 89%
“…Although a study by Toy et al (21) focused mainly on treatment costs and resource utilization, it reported limited information on treatment patterns in patients with metastatic melanoma. Toy et al (21), using a slightly earlier database (spanning from 2010 to 2012), reported the frequency of patients receiving therapy in 834 patients with metastatic melanoma: ipilimumab and vemurafenib were the most frequently used agents (265 [32%] ipilimumab, 234 [28%] vemurafenib).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study published by Toy et al 13 , the costs, resource utilization, and treatment patterns for patients with malignant melanoma were examined for a 6-month period, which included the advent of ipilimumab and vemurafenib therapies. Their population consisted of 834 patients who had at least 1 diagnosis of melanoma (icd-9-cm 172.xx codes), 1 diagnosis of a secondary malignant neoplasm (icd-9-cm 196.xx, 197.xx, 198.xx, 199.xx codes), and who had initiated metastatic melanoma treatment with certain therapies (ipilimumab, vemurafenib, interleukin 2, dacarbazine, temozolomide, paclitaxel) between 25 May 2011 and 30 September 2012.…”
Section: Telehealthmentioning
confidence: 99%